Etymology of Triatomine Species (Hemiptera: Reduviidae: Triatominae) - Gonçalves, Teresa Cristina Monte; Novo, Shênia Patrícia Corrêa; Lopes, Catarina Macedo; Santos-Mallet, Jacenir Reis Dos (Zootaxa, 2009)
Systematics is the branch of biology in which the groupings and biodiversity of living organisms are studied and identified, and its most notable fields are classification and nomenclature. In the present study, 112 species of triatomines for which the original descriptions could be accessed are listed. Among these descriptions, the etymology of the species name has only been mentioned for 82 species. Of these, 14 species form part of the Entomological Collection of the Oswaldo Cruz Institute, the Herman Lent Entomological Collection of FIOCRUZ, and the Rodolfo Carcavallo Entomological Collection of FIOCRUZ. Sixty-six species were named after people, of whom 13 had worked at the Oswaldo Cruz Institute. In an attempt to gather together all this information, this study reports the origins of some of these species names, with their respective bibliographic references according to the original descriptions.